2018
DOI: 10.1177/1526602818764616
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Endograft Apposition, Position, and Expansion in the Aortic Neck Predicts Type Ia Endoleak and Migration After Endovascular Aneurysm Repair

Abstract: Progressive changes in dimensions of the endograft within the infrarenal neck could be detected on regular CTA scans before the complication became urgent in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 23 publications
(37 reference statements)
0
58
1
Order By: Relevance
“…After the 23 full-text papers were read for eligibility, 10 additional studies were removed because eight studies did not include measurement of endograft position relative to an anatomical landmark or endograft apposition with the arterial vessel wall, one study measured these parameters from 2D digital subtraction angiography images, and one study reported measurements on fewer than 10 patients. The remaining 13 studies were included in this review [4][5][6][7][8][13][14][15][16][17][18][19][20]. A flowchart of the selection procedure is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the 23 full-text papers were read for eligibility, 10 additional studies were removed because eight studies did not include measurement of endograft position relative to an anatomical landmark or endograft apposition with the arterial vessel wall, one study measured these parameters from 2D digital subtraction angiography images, and one study reported measurements on fewer than 10 patients. The remaining 13 studies were included in this review [4][5][6][7][8][13][14][15][16][17][18][19][20]. A flowchart of the selection procedure is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis was not performed because of the heterogeneity of study design, patient inclusion, end points, follow-up, and measurement methods. Five studies assessed the endograft in the proximal landing zone in the aortic neck after EVAR [8,14,17,19,20], three studies assessed the distal landing zone in the common iliac arteries (CIAs) after EVAR [6,7,16], and three studies assessed proximal and distal landing zones [4,5,15]. One study assessed the proximal landing zone after TEVAR [13], and one assessed the distal landing zone after TEVAR [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations